Adsorption kinetics and foaming properties of soluble microalgae fractions at the air/water interface. (December 2019) - Buchmann, Leandro; Bertsch, Pascal; Böcker, Lukas; Krähenmann, Ursina; Fischer, Peter; Mathys, Alexander
Abstract: Microalgae as a novel food ingredient are of increasing interest as they can be grown on non-arable land and fixate CO2 when grown photoautotrophically. Here, we employ proteins extracted from Arthrospira platensis biomass to be used for the stabilization of fluid interfaces, which is one of the most important techno-functional applications of proteins. Model foams were prepared from crude A. platensis powder and A. platensis isolate and whey protein isolate as a reference. The derived A. platensis isolate exceeded the overrun and the foam stability of whey protein isolate. The comparable low surface activity of crude A. platensis powder emphasizes the need for the extraction process. The neutral color of the A. platensis isolate indicates that the valuable natural pigments present in A. platensis were retained while achieving relevant techno-functional properties with the residual biomass. Physical treatment with nanosecond pulsed electric fields further increased the biomass yield without impeding the techno-functional properties of the derived isolates. Thus, protein extraction from microalgae biomass is an interesting approach to obtain techno-functional proteins and increase microalgae production efficiency. Graphical abstract: Image 1080727 Highlights: Thorough valorization of Arthrospira platensis biomass. Colorless Arthrospira platensis isolate following isoelectric precipitation. Algae isolate overrun exceeds that of whey protein isolate. Foam stability of algae isolates at acidic pH superior to whey protein isolate. Retained techno-functional properties of algae isolate following nsPEF treatment.